Mosque as an Educational Space: Effectiveness of Management and Implementation of Al-Quran Learning Program - Rahmawati, Ummi; Iribaram, Suparto; Al Jauhari, Shofwan; Deraman (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
Apart from being a place of collective worship, mosques can also be a potential place of Qur'an education for Muslims. However, this context has not been comprehensively discussed in previous studies. This study not only aims to complement the shortcomings of previous studies but also focuses on the question of the function and potential of the mosque as a place of Qur'an education for Muslims. To answer this question, this study chose to use a descriptive qualitative approach by conducting direct and structured observations and interviews with informants. The findings in this study show two important contexts regarding the function and potential of the mosque as a place of Qur'an education for Muslims. First, the management of mosque space can be a potential place in conducting Qur'an education for Muslims as has been done at the Baiturrahmah Mosque. Second, good management of the Qur'an education program can increase interest and shape Muslims to be more active and participatory as happened at the Baiturrahmah Mosque. From these two important findings, it can be reflected that the mosque, apart from functioning as a space for collective worship, can also be a potential place to conduct effective and efficient Qur'an education.